Body mass index and occupational accidents among health care workers in a large university hospital. Issue 2 (4th March 2023) - Fraeyman, N.; De Bacquer, D.; Fiers, T.; Godderis, L.; Verhaeghe, R.; Eeckloo, K.; Gemmel, P.; Viaene, L.; Mortier, E.
ABSTRACT: Introduction: Obesity is associated with a number of chronic diseases such as cardiovascular diseases and cancers. The association of obesity with occupational accidents has been suggested although the evidence is less convincing. The objective of the study is to analyse the relationship between BMI values and ergonomic accidents in a large University Hospital. Methods: The relationship between body mass index (BMI) and the incidence of ergonomic occupational accidents over a period of 8 years was investigated in a cohort of employees of a large University Hospital, covering almost 27, 000 person-years of observation. This relationship was stratified according to the variables age, gender, functional status within the organization and work schedule (part-time or full time). Height and weight were objectively measured, demographic data were obtained from the human resource department and the registration of ergonomic accidents was carried out by the safety and prevention department of the hospital. Results: The number of ergonomic accidents, expressed as number/1000 person-years was higher for female employees compared to male employees, increased with age and markedly increased from functional class A (leading or expert function and higher educational level) to D (executive function in patient care and technical department). However, the incidence of ergonomic accidents accompanied by loss of working time was not significantly associated with BMI, independently of age and gender. In addition, the type of accident and the severity of the accidents expressed as the number of days absent from work were unrelated to BMI. Conclusion: No independent relationship between BMI and the incidence of ergonomic accidents could be identified in our cohort. Tailoring working conditions to individual BMI levels is not recommended.